Insulin resistance and inflammation mediate the association of abdominal obesity with colorectal cancer risk - Li, Wenqiang; Liu, Tong; Qian, Liang; Wang, Yiming; Ma, Xiangming; Cao, Liying; Zhang, Qingsong; Qu, Jun (Frontiers in Endocrinology, 2022)
Abstract Background: The close association of abdominal obesity rather than general obesity with colorectal cancer (CRC) risk might be mediated by IR and inflammation, which has never been systematically explored in large-scale prospective studies. Methods: We prospectively examined the mediation effects of the fasting triglyceride-glucose (TyG) index and C-reactive protein (CRP) on the associations of obesity (general and abdominal) with CRC risk among 93,659 participants. Cox proportional hazards regression models and subgroup analyses were used to calculate the hazard ratios (HRs) and 95% confidence intervals (95% CIs) of CRC. The CAUSALMED procedure was used to perform the mediation analyses. Results: During a median follow-up of 13.02 years, 586 CRC cases were identified. Male participants with general obesity and abdominal obesity had a 1.29-fold and a 1.28-fold increased risk of CRC. However, a significant association was only observed among female individuals with abdominal obesity. Both TyG index and CRP were associated with an elevated risk of CRC, and A significant interaction between the TyG index and CRP was found for the risk of CRC (P for interaction<0.05). CRP and the TyG index significantly mediated the positive association between abdominal obesity and CRC risk. Conclusions: CRP and TyG index increased the risk of CRC independently and synergistically. Mediation effects of CRP and the TyG index were found for the association between abdominal obesity and CRC risk.